2002
DOI: 10.1115/1.1500744
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility as a Differential Indicator of Structural Damage

Abstract: This article discusses the use of frequency domain transmissibility functions for detecting, locating, and quantifying damage in linear and nonlinear structures. Structural damage affects both the system poles and zeros; however, zeros are much more sensitive than poles to localized damage. This is because zeros depend on the input and output locations whereas poles do not. It is demonstrated here that since transmissibility functions are determined solely by the system zeros, they are potentially better indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 6 publications
1
90
0
Order By: Relevance
“…Johnson and Adams [22] showed that transmissibility functions could be used to effectively detect and locate structural changes. Transmissibility functions only contain the zeros, and not the poles, of discrete frequency response functions (FRF), and therefore, contain information about more localized regions of structures.…”
Section: Damage Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson and Adams [22] showed that transmissibility functions could be used to effectively detect and locate structural changes. Transmissibility functions only contain the zeros, and not the poles, of discrete frequency response functions (FRF), and therefore, contain information about more localized regions of structures.…”
Section: Damage Locationmentioning
confidence: 99%
“…When the transmissibility version of the ARX models is used, they can help to detect and locate damage. The reason for this dual capability is that transmissibility functions contain only the transmission zeros of the system and, hence, are more sensitive to local changes in system characteristics [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In [15], transmissibility functions, which only depend on the zeros of the system, are shown to be more sensitive to localized damages than other methods, such as modal analysis, which only monitor the poles (global properties) of the system. The use and the performance of transmissibility functions for damage localization have been investigated also in [16] for chain-like mass-spring systems.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore if we compute the transmissibility functions between consecutive locations, defined on the damaged structure and subtract the same transmissibility functions of the undamaged structure, the damage location should come up with the biggest value of the indicator. Johnson and Adams [6] have also posed a similar indicator:…”
Section: Damage Indicatorsmentioning
confidence: 99%
“…In previous work [5,6] it was shown that the use of transmissibility func-tions for damage detection seems promising. Techniques based on comparing two sets of transmissibility functions of the undamaged and damaged structure have been developed.…”
Section: Introductionmentioning
confidence: 99%